Pengembangan Media Pembelajaran Interaktif Edpuzzle dalam Pembelajaran Sejarah - Purmintasari, Yulita Dewi; Lesmana, Chandra (Universitas Hamzanwadi, 2023)
Learning history is one of the most difficult lessons because of the distance in space and time, so it is necessary to present interactive learning media that make historical values more understandable. The development of Edpuzle interactive video learning media in history learning aims to develop learning media and to determine the effectiveness of the product developed. The research process applies the 4D development research method with the stages of Define, Design, Develop and Deseminate. The research instruments are in the form of expert validation sheets, lift sheets and test questions. The results of the media validation show